1992
DOI: 10.1128/jvi.66.3.1781-1785.1992
|View full text |Cite
|
Sign up to set email alerts
|

Processing of avian retroviral gag polyprotein precursors is blocked by a mutation at the NC-PR cleavage site

Abstract: The avian sarcoma and leukosis viruses (ASLV) encode a protease (PR) at the C terminus of gag which in vivo catalyzes the processing of both gag and gag-pol precursors. The studies reported here were undertaken to determine whether PR is able to cleave these polyproteins while it is still part of thegag precursor or whether the release of its N terminus to form free PR is necessary for full proteolytic activity. To address this question, we created a mutation that disrupts the PR cleavage site between the NC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Previous studies indicated that peptides containing the p2-plO cleavage site competitive inhibitors of the RSV protease in vitro, in agreement with a role in regulation (11). In contrast, peptides containing the NC-PR cleavage site are processed efficiently vitro (10), in agreement with the hypothesis that this site among the first to be cleaved during particle maturation (8). If the p2-plO junction serves to delay activation of PR in vivo, then its replacement with the NC-PR junction should allow premature activation of PR, destabilization of Pr76gag, and concomitant reduction in viral particles released from cells.…”
Section: Lysates Mediasupporting
confidence: 71%
“…Previous studies indicated that peptides containing the p2-plO cleavage site competitive inhibitors of the RSV protease in vitro, in agreement with a role in regulation (11). In contrast, peptides containing the NC-PR cleavage site are processed efficiently vitro (10), in agreement with the hypothesis that this site among the first to be cleaved during particle maturation (8). If the p2-plO junction serves to delay activation of PR in vivo, then its replacement with the NC-PR junction should allow premature activation of PR, destabilization of Pr76gag, and concomitant reduction in viral particles released from cells.…”
Section: Lysates Mediasupporting
confidence: 71%
“…It could result from the initiation of protein synthesis at an internal AUG or be a degradation product resulting from the action of a host-encoded protease. In the case of Myr0, the 66-kDa species has been proposed to be Gag minus the PR sequence, which must be released before other cleavages can occur (8).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, bacterially expressed PR from HIV-1 has been shown to be active when imbedded in a precursor protein (5,6,11,17). Active Rous sarcoma virus PR can also be expressed as a precursor polyprotein; however, the PR activity of the polyprotein is much less than that of the excised PR (1,19).…”
mentioning
confidence: 99%